1991
DOI: 10.1111/j.1439-0442.1991.tb00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Various Adjuvants on the Synthesis of Specific Antibodies of Chicken, Sheep and Rabbit Following Immunization with an Hapten*

Abstract: Summary In order to obtain high amounts of specific antibodies against the hapten methylphosphoric acid, para‐aminophenyl‐1,2,2‐trimethyl‐propyldiester (MATP) different animals were immunized with MATP coupled to the carrier protein human serum albumin (MATP12‐HSA) using several adjuvants. The best specific immune response in sheep, rabbit and chicken was reached with Freund's complete adjuvant with animal specific differences being tested by an ELISA. The adjuvants aluminium hydroxide (5% and 10%) and diphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…To ex- Our data suggest that the source of the carrier protein primarily affects the antibody amount generated. Investigations similar to those described here using a non-rabbit protein as carrier led to considerably higher titers (12) but not to significant changes in antibody affinity. Consistent with a previous study (21), we found that a carrier protein derived from the same species as the immune host is immunologically not inert.…”
Section: Measurement Of Relative Antibody Affinity Distributionsupporting
confidence: 51%
See 1 more Smart Citation
“…To ex- Our data suggest that the source of the carrier protein primarily affects the antibody amount generated. Investigations similar to those described here using a non-rabbit protein as carrier led to considerably higher titers (12) but not to significant changes in antibody affinity. Consistent with a previous study (21), we found that a carrier protein derived from the same species as the immune host is immunologically not inert.…”
Section: Measurement Of Relative Antibody Affinity Distributionsupporting
confidence: 51%
“…(15). The production of anti-MATP polyclonal or monoclonal antibodies (mAbs) obtained by using non-rabbit protein as carrier protein has been described recently (12,18,19). These rabbit antisera and four …”
Section: Syntheses Of Hapten-carrier Conjugatesmentioning
confidence: 99%
“…TiterMax™, Ribi™, and Gerbu™ adjuvants) have been invented to generate a potent immune response with significantly reduced toxicity (Stils, 2005;Algate et al, 2013), but most of the evaluation studies were focused on developing antibodies to macromolecules. Only a few investigations have been carried out to find replacements for Freund's adjuvants in the production of hapten-specific antibodies (Erhard et al, 1991;Fodey et al, 2008;George et al, 2012;Maquieira et al, 2012;Parra et al, 2013).…”
Section: Introductionmentioning
confidence: 99%